Gender As A Moderator Of The Effect Of Attitude Toward Entrepreneurship, Perceived Behavioural Control On Entrepreneurial Intention - Ardika Melsalasa Sahputri, Rindi; Artha Tsary Rumalessin, Ummu; Alamsyah, Redi; Ali, Hendrik; Olis Vera, Lusi; Ray Gucchi, Anjaka (Journal of Community Development and Disaster Management, 2025)
This study aims to explore the role of gender on the relationship between attitude toward entrepeneurship, perceived behavioural control and entrepreneurial intention in vocational students in Indonesia. The data were gathered from several universities, comprising 600 students. Multigroup structural equation modeling was used to estimate the moderating effect of gender on the relationship. The result found that gender had weak effect on entrepeneurial intention, when it was treated as an independent variable, mediated by attitude toward entrepenurship and perceived behavioural control. However, the result indicates a significant effect of gender when it was treated as moderator. The significant moderating effects were found in the relationship between choice intention, self-efficacy and commitment, and between instrumental attitude and nascent entrepeneurship, as well as commitment and nascent entrepeneurship.